A 6LoWPAN OPNET simulation model for machine‐to‐machine communications. Issue 11 (8th September 2020) - Chen, Dong; Khan, Jamil Y.; Brown, Jason; Awais Javed, Muhammad; Zhuang, Yuan
Abstract: The low‐power short‐range networks have gained prevalence in research fields such as machine‐to‐machine communications and the Internet of things. Given the large number of devices that may exist, the IPv6 over low‐power wireless personal area networks (6LoWPAN) standard is expected to be widely used. Although Contiki, NS‐3, and OMNeT++ have developed the 6LoWPAN model, it is still not available in optimized network engineering tools (OPNET) because it is extremely difficult to interface the built‐in IP module with the customized modules in OPNET. To bridge this gap, we first developed a preliminary 6LoWPAN model and implemented the header compression and header restoration functions to handle the incoming and outgoing packets in OPNET. To further improve the system performance, we also proposed an algorithm that aggregates packets, reduces intranetwork collisions and increases the packet delivery ratio. The model and algorithm in this work are free to download, so researchers from the OPNET community can easily extend this work for their own research in the future. Abstract : How to make a 6LoWPAN simulation model in OPNET?